The Application of Room Attendant Empathy in Service at Aston Batam Hotel & Residence - Elvia Ratna Sari; Lapotulo, Nensi; Afriani, Miratia; Pratama, Tito (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This study aims to explore the application of room attendant empathy in services at Aston Batam Hotel & Residence. Empathy plays a crucial role in the hospitality industry, as it may enhance guest satisfaction and loyalty. However, limited research has been conducted on the specific application of empathy by room attendants in hotel settings. The study will employ a descriptive qualitative research design, utilizing in-depth interviews and observations to gather data. The informants used to select a diverse group of housekeeping departments from Aston Batam Hotel & Residence. The participants will be chosen based on their experience, tenure, and willingness to participate in the study. The data collected will be analyzed, allowing for the identification of recurring patterns and themes related to the application of empathy by room attendants. The analysis will focus on understanding the application of empathy, the ways employed by room attendants to demonstrate empathy, and the impact of empathy on guest satisfaction. The research results show that the application of room attendant empathy in service at Aston Batam Hotel & Residences has a positive impact on guests. In-depth understanding of room attendants in practicing and applying empathy in providing services, more sensitive to guest needs and room attendants trying to fulfill them as best as possible. Keywords: Empathy; Service; Room Attendant; Hotel